Marcuse and “One-dimensional Law” - Trazegnies Granda, Fernando de (1969)
The article breaks down Herbet Marcuse's critique of one-dimensional law, the same law that professes a pure and hard law, or rather, legal positivism that rejects the linking of the legal world with other sciences. Thus, one-dimensional law based on the formalism that characterizes it is not capable of questioning the imposed order it has created, regardless of whether it is good or bad. For Marcuse, norms cannot be promulgated independently of the social reality that surrounds them, since law is and will be a manifestation of the "historical praxis of men". Therefore, it must be created under the ends that society pursues. From this, Marcuse points out that law, besides being a reflection of society, has as its main mission to be an instrument that emancipates man from repression; that is to say, a source that promotes freedom, through the eroticization of life, and no longer as a mechanism that mainly limits and controls the egoistic impulses of the human being.